Implementasi Metode Additive Ratio Assessment (Aras) Untuk Seleksi Siswa Berprestasi Smk Negeri 2 Kota Bengkulu - Eko Febrianto; Indra Kanedi; Devi Sartika (Jurnal Media Infotama, 2022)
Abstract :The data processing process at the Bengkulu City 2 State Vocational High School to select and select outstanding students still uses the manual method. ). The ARAS method is a method based on the intuitive principle that alternatives must have the largest ratio to produce an optimal solution. The ARAS method performs ranking by comparing the value of each criterion on each alternative by looking at the weights of each to obtain the ideal alternative. In the ARAS method, the value of the utility function that determines the complex relative efficiency of feasible alternatives is directly proportional to the relative effect of the value and weight of the main criteria considered for determining the best alternative. From this research, it can be concluded that the student on behalf of Benny Irawan is declared as an outstanding student with a ranking value of 0.894